Discourse and language learning across L2 instructional settings. - Soler, Eva Alcon (Utrecht studies in language and communication., 2012)
Studies on discourse and language learning originated in the field of general education and they focused on first language learning environments. However, since 1980s research on discourse and language learning broadened the scope of investigation to resp.